Procedural justice, participation and power distance: Information sharing in Chinese firms - (:unkn) unknown (My University, 2010)
Purpose - The purpose of this paper is to investigate the extent to which procedural justice influences a manager's decision-making behaviour and the extent to which managerial values related to power-distance moderates the relationship between participation in decision processes and procedural justice. Design/methodology/approach - A questionnaire survey was conducted in this study. Dependent variables were the degree of participation in decision making and the degree of sharing information with subordinates. Independent variables were procedural justice and power distance. Findings - The findings suggest that procedural justice is related positively to encouraging initiatives and information sharing. The findings also indicate that power distance moderates the relationship between procedural justice and decision-making behaviours. Although managers were inclined to share information with employees when they believed in procedural justice, high-power-distance values would weaken such a positive link. Research limitations/implications - The study explores the moderating role of power distance in the formation of perceptions about procedural justice but the interactive and distributive justice of managers are not included here for a comprehensive understanding of organizational justice. Another limitation is that the sample in the study was limited geographically to the regions of Southern China. Practical implications - Emphasis of procedural justice among managers throughout the hierarchical system of an organization would be an effective way to improve both management effectiveness and employee performance. However, while managers develop warm relationships with their employees, they still share information reluctantly with employees in decision making when the intent is to maximize power. Originality/value - The perspective of managers, which is adopted in this study, makes it original compared to previous studies of procedural justice. Such studies take the standpoint of employees or student subjects. Another contribution is that the cultural construct of power distance is analysed with managers at the individual level. Further, the study sheds light on important managerial issues related to the relationships between procedural justice, participation and the moderating effects of a manager's value orientation within the context of China. © Emerald Group Publishing Limited.
Keywords: China; Employee participation; Information control; Management power; Managers